Female social media influencers in the Arab Gulf: shaping marketing and advertising on Instagram - Alsalloum, Afrah A.; Gainous, Jason (Frontiers in Communication, 2025)
This study examines the growing influence of female social media influencers in the Arab Gulf, particularly focusing on how they shape marketing strategies through Instagram. These influencers leverage a blend of emotional and rational marketing, effectively engaging audiences by emphasizing three core elements: authenticity, confidence, and interactivity. By building trust, projecting authority, and fostering two-way communication, these influencers connect with followers both on a personal level and through practical product endorsements. This dual approach not only enhances brand perceptions but also drives consumer behavior. Using a qualitative analysis of five prominent female influencers, the study highlights how emotional appeals like storytelling and self-expression are complemented by rational strategies emphasizing product attributes and benefits. The findings contribute to understanding how these integrated marketing tactics influence consumer attitudes, brand loyalty, and purchasing decisions in the digital era.